Peculiar diets and food taboos in the Ancient Thrace (Research Announcements "Heritage BG", 2025)
Written sources and interdisciplinary analysis provide evidence for the existence of peculiarities in the diet of ancient Thracians, including abstinence for a limited period of time (fasting?) or a complete ban on the consumption of certain foods. In some cases, documented food taboos draw a line between the general population and small isolated groups who have the privilege of eating differently. The information about the food that the Thracians refuse / restrict or are forbidden to accept could reveal more about their cultural identity and self-determination. It is even possible for certain social groups and classes to declare themselves through the food they do not consume. The existing special dietary regimes of the Thracians and their neighbors – Greeks and Scythians – could even be considered as an ethno-distinctive marker for the different nations of the Balkans. References:Bayrakov 2014: Bayrakov, Dimitar. Planinski svetilishta v Yuzhna Trakiya. PhD Dissertation, Faculty of History, Sofia University ‘St. Kliment Ohridski’. Sofia.Galabova, Atanasova 2018: Galabova, Borislava, Nadezhda Atanasova. Antropologichen analiz na kostni ostanki, otkriti v arheologicheski obekti ot Balgariya. Razkopki 2015 g. – Interdistsiplinarni izsledvaniya, No. 25, 5-38.Georgieva 1999: Georgieva, Rumyana. Hrana i hranene (kraya na ІІ-І hil.pr.n.e.) Etnologiya na trakite. In: Etnologiya na trakite (eds. Rumyana Georgieva, Tosho Spiridonov, Mariya Reho). Sofia, 71-111.Georgieva 2005: Georgieva, Rumyana. Kanichka ot Karnobat s izobrazheniya na trakiyski voyn. - Arheologiya, No. 1/4, 32-40.Katincharova 2003: Katincharova, Daniela. Grob na voyn ot elinisticheskata epoha pri Tsrancha Arheologiya No. 44/4, 5-13.Popov 1989: Popov, Dimitar. Zalmoksis. Religiya i obshtestvo na trakite. Sofia.Ribarov, Boev 1997: Ribarov, Georgi, Zlatozar Boev. Kostni ostanki ot divi i domashni zhivotni ot praistoricheskoto selishte „Telish-Redutite“ pri s. Telish (Plevensko). – Historia naturalis bulgarica, No. 7, 61-70.Yordanov, Cholakov 2005: Yordanov, Yordan, Slavcho Cholakov. Antropologichno prouchvane na nekropolite ot zhelyaznata epoha v Isperihska obshtina. In:  Helis IV. Izsledvaniya, rezultati i problemi v ‘Sboryanovo’ (ed. Diana Gergova). Sofia, 108-123.Ailincăi 2016: Ailincăi, Sorin-Cristian. Before the Greeks. The Early Iron Age in Dobrudja. In: Prehistoric settlements: social, economic and cultural aspects. Seven studies in the Carpathian area (eds. Florin Gogâltan, Cristina Cordoş). Cluj-Napoca, 201-236.Bartosiewicz 2009: Bartosiewicz, Lászly. A Lion’s Share of Attention: Archaeozoology and the historical record. – Acta Archaeologica, No. 60/1, 275-289.Bianucci, Landini 2007: Bianucci, Giovanni, Walter Landini. Cetacea: An Historical Overview. In: Reproductive Biology and Phylogeny of Cetacea. Whales, Dolphins and Porpoises (ed. Debra Lee Miller). Enfield, NH, 1-33.Davies 1971: Davies, Robert William. The Roman Military Diet. – Britannia, No. 2, 122-142.Dimitrova 2021: Dimitrova, Diana. Zhaba Mogila Cult Complex Near the Town of Strelcha. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 126-131.Ekroth 2007: Ekroth, Gunnel. Meat in Ancient Greece: Sacrificial, Sacred or Secular. – Food & History, No. 5/1, 249-272.Finke 2013: Finke, Roger. Origins and Consequences of Religious Restrictions: A Global Overview. – Sociology of Religion, No. 74/3, 297-313.Fol 2020: Fol, Valeria. Thracian Secret Societies. Sofia.Franko, Moore, O’Bryhim, Olson 2001: Franko, George Fredric, Timothy J. Moore, Shawn O’Bryhim, S. Douglas Olson. ‘ACHARNIANS’. In: Greek and Roman Comedy: Translations and Interpretations of Four Representative Plays (ed. Shawn O’Bryhim). Austin, University of Texas Press, 36-82.Haimovici 2003: Haimovici, Sergiu. The Study of the Archaeozoological Remains from Cogealac (Constanţa County) Belonging to the Helenistic Period – Studia Antiqua et Archaeologica, No. 9, 253-260.Jotischky 2011: Jotischky, Andrew. A Hermit’s Cookbook: Monks, Food and Fasting in the Middle Ages. London & New York.Kisyov 2021: Kisyov, Kostadin. Necropolis near Chernozem Village, Plovdiv Region Tumulus No. 1. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 42-51.Popova 2021: Popova, Ruja. Tholos Tomb below the Tyulbeto Tumulus Kazanlak. In: Cinnabar – the Royal Colour in Thracian and Roman Cultures in the Bulgarian Lands (eds. Valeria Fol, Ruja Popova, Rossitsa Manova). Sofia, 52-61.Ribarov 1991: Ribarov, Georgi. The Osteological Material from Sunken settlement at Ourdoviza. – Actes du symposium International ‘Thracia Pontica’, No. 4, 113-119.Sallares 1991: Sallares, Robert. The Ecology of the Ancient Greek World. Ithaca, New York, Cornell University Press.Venedikov 1977: Venedikov, Ivan. The Archaeological Wealth of Ancient Thrace. – The Metropolitan Museum of Art Bulletin, No. 35/1, 7-71.
Keywords: Thracians; horse meat; lion meat; fasting; identity